WACANA POLITIK PENDIDIKAN DALAM PERKEMBANGAN DEMOKRASI DI INDONESIA - Husniah Ramadhani Pulungan (FORUM PAEDAGOGIK, 2019)
The political education discourse in the development of democracy in Indonesia has influenced the progress of the education system. This is inseparable from the long process of history with various educational political products that have been produced that contribute to the progress of the nation's education. The political education discourse in Indonesia is still proceeding in producing an ideal democratic system. In political discourse, education is still used as one of the main issues in raising public confidence in the leaders, starting from colonialism, a new era, reformation to the present. Thus, the politics of education is one important thing in realizing a positive symbol of democracy in Indonesia.